Optimization of Tissue Handling and Processing in the Era of Precision Medicine: A Practical Recommendation from a Multidisciplinary Panel of Indian Experts - Rajiv Kumar Kaushal; Santosh Menon; Omshree Shetty; Tanuja Shet; Sangeeta Desai; Anurag Mehta; Anuradha Choughule; Bivas Biswas; Divya Midha; Gurudutt Gupta; Jaya Ghosh; Jay Mehta; et al. (Indian Journal of Medical and Paediatric Oncology)
Molecular analysis of biospecimens is the key to diagnostic and therapeutic decisions in clinical practice. However, there is a lack of consolidated guidelines for biospecimen collection, tissue handling, and storage in India. Therefore, this study aims to generate expert recommendations for the optimization of tissue handling and processing practices in India in the era of precision medicine. This study aimed to evaluate the clinical gaps related to tissue handling for molecular analysis and develop expert recommendations to mitigate preanalytical issues associated with biospecimen processing. These expert recommendations will help in increasing the diagnostic yield and accuracy of biomarker testing in clinical practice. A virtual advisory board meeting was convened with 19 experts, including pathologists, molecular biologists, medical oncologists, surgical oncologists, interventional radiologists, and a senior histology technician from 10 hospitals in India, along with an accreditation officer for testing and calibration of laboratory procedures. The scientific coordinators developed specific questions to address the salient issues associated with the preanalytic phase of tissue specimen preparation. The experts discussed each question until a complete set of recommendations was obtained. The expert panel provided recommendations for tissue collection, processing, fixation, and block preparation to ensure high-quality biospecimens. As per the expert panel recommendations, tissue sampling can be performed from any easily accessible site, regardless of the primary or metastatic locations. In addition, the cold ischemia time should be <1 hour, 10% neutral-buffered formalin should be used as the fixative, isopropyl alcohol should be used as the dehydrating agent, the volume of tissue to fixative ratio should be 1:10, and all the paraffin blocks should be archived in dry, pest-free conditions at room temperature. The experts suggested that the formalin used for fixation should be freshly prepared and its pH should be checked daily; moreover, the pH and date of formalin preparation should be mentioned on the containers. The experts highlighted the need to educate multidisciplinary teams on the optimization of tissue handling practices and emphasized that a pathologist should always check the tissue for adequate quality and quantity for biomarker testing. The existing routine clinical procedures for collecting and handling biospecimens adversely affect their quality. The expert recommendations for preanalytical quality control would ensure high-quality biospecimens for molecular analysis and precision medicine.